Examining Education Students’ Preference for Reading Medium, Resource and Time - Sharma, Lok Raj (International Research Journal of MMC, 2020)
The chief purpose of this research article is to examine the Bachelor of Education students’ preferred reading medium, resource and time for their academic purpose. It is based on the cross sectional survey carried out at Makawanpur Multiple Campus, Nepal across the boy and girl students in 2020. The simple random sampling technique, especially lottery method was applied to select 126 students from the population of 185 students. The researcher used a questionnaire regarding the students’ preference and reasons for reading medium, resource and time. The percent statistics show that 70.6% students preferred the print medium and 29.4% students preferred the print medium. The students who preferred teachers’ hand-outs, text books, guide books and solution books were 42.2%, 19.8%, 19.0% and 19.0% respectively. The students who preferred morning time, day time and evening time were 61.1%, 23.8% and 15.1% respectively. The chi-square test of independence between sex and preferred reading medium [ χ2 (1) = 2.391, critical value = 3.841 and p (.122) > .05]; between sex and preferred reading resource [ χ2 (3) = 2.595, critical value = 7.815 and p (.458) > .05]; and between sex and preferred reading time [ χ2 (2) = .620, critical value = 5.991 and p (.733) > .05] show that there was no statistically significant association between sex and preferred reading medium, resource and time.